ISLAMIC COMMUNICATION FROM A CRITICAL PERSPECTIVE: POWER RELATIONS, DISCOURSE, AND RELIGIOUS AUTHORITY - Muhammad Obie (UIN Kiai Ageng Muhammad Besari Ponorogo, 2026)
This study analyzes Islamic communication from a critical perspective by examining the relationships among power, discourse production, and the construction of religious authority in the digital era. This study employs a qualitative approach, integrating Critical Discourse Analysis (CDA) with a sociological perspective on communication. The empirical data consist of 12 digital da’wah content items collected from YouTube, Instagram, and Spotify podcasts published between January and March 2025. Data were collected through document analysis of verbal transcripts, captions, audience interactions, and non-participant observation of communication practices in digital religious spaces. Data analysis follows Fairclough’s three-dimensional framework, including textual analysis, discursive practice, and social practice. The findings reveal that Islamic communication in digital spaces functions not merely as a medium for transmitting religious messages, but also as a contested arena where actors negotiate symbolic power and construct religious legitimacy. The study further demonstrates that digital media reconfigures religious authority from institution-based legitimacy to audience-driven, algorithmically mediated authority. Theoretically, this study contributes to Islamic communication studies by integrating discourse, power, and digital religious authority into a critical analytical framework.